2021
DOI: 10.3390/cells10092278
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower mosaic virus P6 Dysfunctions Histone Deacetylase HD2C to Promote Virus Infection

Abstract: Histone deacetylases (HDACs) are vital epigenetic modifiers not only in regulating plant development but also in abiotic- and biotic-stress responses. Though to date, the functions of HD2C—an HD2-type HDAC—In plant development and abiotic stress have been intensively explored, its function in biotic stress remains unknown. In this study, we have identified HD2C as an interaction partner of the Cauliflower mosaic virus (CaMV) P6 protein. It functions as a positive regulator in defending against CaMV infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Thus, our data suggests that CaMV benefits from disruption of ABA homeostasis and indeed, we also found that ABA responsive genes are widely affected by CaMV and highly deregulated when compared to ABA treatment (Hoth et al ., 2002). This could at least partially be attributable to the CaMV P6 protein interacting with and repressing the function of histone deacetylase H2DC, a regulator of ABA-mediated gene expression (Li et al ., 2021; Sridha & Wu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data suggests that CaMV benefits from disruption of ABA homeostasis and indeed, we also found that ABA responsive genes are widely affected by CaMV and highly deregulated when compared to ABA treatment (Hoth et al ., 2002). This could at least partially be attributable to the CaMV P6 protein interacting with and repressing the function of histone deacetylase H2DC, a regulator of ABA-mediated gene expression (Li et al ., 2021; Sridha & Wu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“… 29 In cauliflower mosaic virus (CaMV) infection plants, the global levels of histone acetylation are increased, and the infection of CAMV is promoted. 73 However, to date, changes in acetylation levels after TMV infection have seldom been reported. The acetylated proteins identified in our putative study may be involved in the pathogenic process of viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fungal pathogens promote susceptibility in soybean and maize through altering protein acetylation . In cauliflower mosaic virus (CaMV) infection plants, the global levels of histone acetylation are increased, and the infection of CAMV is promoted . However, to date, changes in acetylation levels after TMV infection have seldom been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The HD2-class HDAC AtHD2B was identified as targeted by the MAPK-type kinase MPK3 to re-localize from nucleolus to nucleoplasm to repress the transcription of flg22-regulated genes and biotic stress-responsive genes ( Latrasse et al, 2017 ). More recently, another HD2-class HDAC AtHD2C was identified as a positive regulator of plant resistance to Cauliflower mosaic virus (CaMV) infection ( Li et al, 2021 ). AtHD2C is involved in silencing viral genome by decreasing histone acetylation on viral minichromosome.…”
Section: Histone Modification Regulators Involved In Plant Response T...mentioning
confidence: 99%
“…As counteraction, the CaMV P6 protein physically interacts with AtHD2C and interferes with the interaction between AtHD2C and HDA6, leading to HDAC dysfunction and thus promoting CaMV infection. Correspondingly, the susceptibility to CaMV infection is increased in the hd2c mutants ( Li et al, 2021 ). The wheat ( Triticum aestivum ) HD2-class HDAC TaHDT701 can stabilize the interaction between TaHDA6 and HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES 15 (TaHOS15), forming a larger HDAC complex involved in plant resistance to wheat powdery mildew ( Zhi et al, 2020 ).…”
Section: Histone Modification Regulators Involved In Plant Response T...mentioning
confidence: 99%